Faktor-Faktor Peningkatan Permohonan Dispensasi Nikah Di Pengadilan Agama Panyabungan Pada Masa Covid-19 - Uswatun Hasanah (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
The Marriage Dispensation is a way out for parties who wish to marry, but still below the age limit set by the Act. The limitations contained in Law No. 1 of 1974 jo. Law No. 16 of 2019, namely the age of 19 years for women and men. During the Covid-19 pandemic, there was an increase in applications for marriage dispensation at the Panyabungan Religious Court. The factors that cause it are due to personal desires, economic factors, parental factors and already pregnant without marriage.  Kata Kunci: Covid-19, Dispensasi Nikah, Peningkatan